On Pina Bausch’s Legacy: an interview with Dominique Mercy - Dominique Mercy; Marcelo de Andrade Pereira (Revista Brasileira de Estudos da Presença, 2018)
Perhaps no other author has better characterized the work of Pina’s dancers – and, therefore, the artist’s herself – than José Sasportes – a remarkable Portuguese dance critic and historian. This brief observation of Sasportes, made in a text entitled Acção para bailarinos [Action for dancers], and regarding an event held in Lisbon in honor to Pina Bausch, allows to perceive in quite clearly the meaning of the experience and legacy of a remarkable artist, that are summarized in the figure of one of her greatest collaborators, Dominique Mercy. Certainly, there is no need to introduce Dominique. It is worthy, though, to recover some moments that preceded his fortuitous encounter with Pina in the early 1970’s in Saratoga, United States. Born in 1950 in the city of Mauzac, France, Dominique’s first professional steps in the dance world from the mid-1960’s on were in the Bordeaux Grand Théâtre, later followed by the Amiens Ballet du Art Contemporain. In 1973, two years after his first encounter with Pina in the Summer Festival of Saratoga, in 1971, Dominique goes to Germany, to Wuppertal, to be part of the recently founded Tanztheater. His close relationship with Pina allowed, in fact, that her legacy could be kept alive following her sudden death in 2009. Dominique took over the artistic direction of the Company with Robert Sturm for some of the following years, having later transferred the position to his co-worker and dancer Lutz Forster. It was beside Pina and so many others from the Wuppertal ensemble that Dominique ended up writing one of the major pages in the annals of dance history in the 20th century. The experience of – or rather, with – Pina that each one of us apparently has with her when meeting her work for the first time, allowing to understand in a certain extent the fascination that she exerts until nowadays on the audience, passes as well and indispensably through those who worked with her and by her means. My first time with Pina was, for sure, beside Dominique Mercy, or rather, in front of him. Dominique was half-naked, wearing only a tutu and carrying a watering can. It was 2006, for the presentation of Fur die kinder von gestern, heunte und morgen, in Porto Alegre. Pina was also there. The unusual encounter – even though separated by the proscenium arch – would happen again years later in Paris. However, this time, in 2011, without Pina and with no line dividing us. I was introduced to Dominique following one of the presentations of Como el musguito em la piedra..., by the also Tanztheater Wuppertal dancer Daphnis Kokkinos. On that occasion, Dominique had an extremely light and welcoming attitude. Over the years, I noticed that it was not a protocol way of introduction, but